IN PROCESS QUALITY CONTROL FACTORS EFFECTING POTENCY OF PESTE DES PETITS RUMINANTS VIRUS VACCINES IN GOATS - M. Anees; K. Muhammad; M. Rabbani; M. Younus; J. Nazir; K. Hanif; Q. Akram; 1M. H. Raza (Journal of Animal and Plant Sciences, 2014)
Pesti des Petits Ruminants (PPR) is an acute contagious viral disease of small ruminants and is causing heavy economic losses to goat industry. It is controlled by mass vaccination and bio-security measures. In present study, in process quality control factors such as variable biological titer, different adjuvants and shelf life of the PPR vaccines affecting antibody response of the goats were evaluated. The freeze dried vaccine with a biological titer of 105.00 TCID50 per dose provoked maximum antibody titer followed by the ones with a titer of 104.00 or 103.00TCID50 which provoked nearly equivalent antibody response while the goats inoculated with a vaccine having 102.00 TCID50 virus concentrations developed minimum antibody titer. The oil based PPR virus vaccines elicited significantly higher antibody response (p<0.05) while gel based vaccines induced relatively less antibody titer but freeze dried PPR vaccine induced minimum antibody titers. Each of the adjuvant vaccines (oil or gel) and non- adjuvant vaccine containing biological titer of 104.00 TCID50 induced more than 50 Percent Inhibition (PI) values (protective antibody titer). The freeze dried vaccine stored at 4 °C did not show any significant drop in the biological activity of the virus even after 12 months of the storage. Moreover, both the freeze dried and adjuvant vaccines when stored for 12 months at 4 °C did not show any effect on their antibody response in the vaccinated goats. It is concluded that oil adjuvant vaccine with 104.00 TCID50 units of biological titer of virus induced the highest antibody titer in goats that persisted for more than 10 months post priming.
Keywords: PPR vaccine; goats; adjuvant; antibody response